Structure Of Tongkonan Traditional House Buildings As A Source Of Physics Learning - Fajriyani Fajriyani, (Al-Khazini: Jurnal Pendidikan Fisika, 2023)
Learning by utilizing the uniqueness of culture has been rampant to attract students. Starting from food, dance, and even traditional houses can be used as learning resources. Tongkonan is a traditional house typical of the Toraja tribe that has a unique culture that has been studied by many researchers in terms of history, culture and architecture. However, there are still few who relate it to science learning. This study aims to identify physics concepts contained in the Tongkonan traditional house that can be used as a source of physics learning. The method used in this research is qualitative research with the form of literature. The results showed that in the construction of Tongkonan traditional house, several physics concepts can be identified as physics learning resources, including density and elasticity associated with the main materials in the construction of Tongkonan traditional house. The concept of equilibrium of rigid bodies and rotational dynamics can be obtained in the installation of poles and the roof of the house. The concept of forces and pressure also discussed on the construction of the Tongkonan traditional house in the preparation of the roof and the meeting between the pole and the foundation.